Structural dynamic modification of vibrating structures using topology optimization / Sajjad Zargham - Sajjad, Zargham (2012)
This thesis presents a structural dynamic modification of vibrating structures by using topology optimization method in order to find the most effective design of a structure supporting rotating machinery. Modal testing and operating deflection shape (ODS) measurement were applied to identify the dynamic characteristics of a pedestal structure. The dynamic characteristics of the structure were ascertained to validate the finite element model. Then, topology optimization method was used to determine the optimum design of the structure. Results from modal testing showed that the structure has two natural frequencies at 12.1 Hz (left to right bending), and 16.7 Hz (rear to front bending). The ODS measurement indicated the exact deflection shapes of the structure related to these two natural frequencies. Afterwards, a topological optimization was applied to ascertain optimized design of the structure. It was observed that, by applying the finite element modal analysis to the new design, both of the natural frequencies were shifted from 12.1 Hz and 16.7 Hz to 27.5 Hz and 25.7 Hz, respectively. Accordingly, there would not be any natural frequency within the motor operating frequency range. In addition, by applying some conditions on designable area and optimization constraint, proposed design has advantage of uncomplicated manufacturability. As a result, topology optimization method is capable of getting optimum design in less time and a more effective way in comparison with trial and error methods.